Flood Disaster Management Training (FDMT) to Improve Family Preparedness: Knowledge, Perceptions, Attitudes and Abilities - widya addiarto; Achmad Kusyairi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2025)
Currently, the main problem that occurs is the high number of flood disasters which have a very large impact on people's lives. This flood disaster has not been matched by community preparedness in flood-prone areas. Most of them still do not have preparedness in responding to disasters that threaten every year. Therefore, efforts are needed to increase the preparedness of at least the closest family to gain knowledge and ability to respond to existing disaster events. The purpose of this study was to find out how FDMT influences family preparedness. The research design used was a pre-experimental design with a one group pre post test design approach. The sample was selected by purposive sampling technique with a sample of 60 respondents. Furthermore, respondents were asked to fill out a questionnaire first (pre-test) then given an intervention. Then at the end of the activity the respondent will be given a questionnaire (post test) about family preparedness, These variables include: knowledge, perceptions, attitudes and abilities. The results showed that all sub-variables of family preparedness experienced a significant increase before and after the intervention, namely: knowledge increased (p = 0.000), perception (p = 0.021), attitude (p = 0.001) and ability (p = 0.000). From the results of this study it can be concluded that the FDMT intervention is effective in increasing family preparedness so that it can be used for disaster management training for the community.